Dewan Direksi Wanita dan Komite Keberlanjutan dalam Mengungkapkan Emisi Karbon - Indah Sulistyowati; Tumirin Tumirin (Universitas Muhammadiyah Gresik, 2023)
The purpose of this study is to examine the influence of female directors and sustainability committee on carbon emission disclosure. The population was companies in the sector of agriculture, energy, and industry period 2019-2021 listed on the Indonesia stock exchange (IDX). Based on the purposive sampling method, 27 companies were selected as the samples (81 firm year observations).The data analysis technique used is multiple linier regression. The results showed that the female directors do not has a effect on carbon emission disclosure, while sustainability committee has a positive effect on carbon emission disclosure.